3D Separable 2-layered Elastic Models of the Face for Surgical Planning of Local Flaps. Issue 7 (July 2018) - Okamoto, Toyoko; Hirota, Yuka; Kimura, Yusuke; Senda, Erina; Ueda, Koichi
Abstract : Summary: Reconstruction with the use of local flaps always involves 3 dimensional movements. It is difficult to predict with 3D complex forms stereoscopic changes after local flap operations on the face. We have made 3-dimensional computer-assisted 2-layered elastic models of the face. The surface layer of the model can be detached from the inner layer. By observing the surface model after simulation surgery, it becomes possible to note the distortions caused by the flaps and to determine the tension of each stitch during suturing of the flap. For the simulation surgery, we used our model for a 73-year-old woman with basal cell carcinoma of the nose, selecting the best of several candidate flaps. The time of removal of the stitches could be delayed at the places with high tension. By using these separable 2-layered models of the face, we can choose the best reconstruction method. The actual operation can be performed smoothly, and the best time to remove the stitches can be determined.